DOCTOR MIGRATION: UNPACKING ECONOMIC AND SOCIAL IMPACTS - Mahir Tosunoğlu; Tunahan Aslan; Andrzej Cieślik; Turgud Valiyev (Agora International Journal of Economical Sciences)
Health expenditures are vital indicators of a nation’s social and economic progress, playing a key role in welfare and sustainable development. A well-functioning healthcare system relies on an adequate and skilled workforce, yet many countries face shortages, prompting reliance on international labor migration. This study investigates the economic and social drivers of health labor migration, focusing on doctors in 15 high-income countries from 2011 to 2019. Using panel data analysis, we found that lower wages significantly drive migration, with a 1% increase in wages reducing health worker migration by 0.08%. The results underscore the importance of fair remuneration in retaining healthcare professionals within their home countries. Moreover, destination countries with better training infrastructure and career advancement opportunities create additional pull factors, compounding the challenges faced by source countries. Globalization further facilitates migration by lowering barriers and harmonizing professional standards. These findings highlight the urgent need for policy interventions to address wage disparities and mitigate brain drain while ensuring global health workforce equity.